Estimation and Evaulation of Collagen Fibres as Stromal Componment in Various Grades of Oral Squamous Cell Carcinoma Using Picrosirius Red Stain under Polarised Microscope - Nayak, Manjushree; Panda, Jayanta Kumar; Mishra, Sudha Smruti; Das, Bijay Kumar (International Journal of Innovative Research in Medical Science, 2019)
Oral squamous cell carcinoma (OSSC) is the 3rd most common form of malignancy in developed countries[1]. The tumour is composed of two basic components i e, the neoplastic cells and the reactive stroma. The stromal changes which indicate the propensity of tumour cells to infiltrate and metastasise can also be used as one of the prognostic indicator[4,5]. Use of Picrosirius red (PSR) stain along with circular polarising microscope is helpful to detect spread of malignancy and guides the treatment plan and assess prognosis[11]. The present study is aimed to analyse the various aspects of collagen fibres in relation with the different grades OSSC. 30 patients of OSCC of various grades and 10 cases of normal mucosa were evaluated and data analysed statistically using sigma scan pro image analysis software(SPSS). Observation: Thirty patients (male-19 and female -11) of OSCC of age group 47-60 years were analysed. There were 14 well differentiated (WDSCC), 12 moderately differentiated (MDSCC) and 4 poorly differentiated (PDSCC) cases. When examined under polarising microscope majority (85.7%) of WDSCC and 41.67% of MDSCC showed reddish orange (RO) collagen fibres whereas in PDSCC (50%) showed green yellow (GY) collagen fibres which is statistically significant (P=0.02).In WDSCC 57.14% and in MDSCC 50% had swirl(S) arrangement whereas in PDSCC 50% had crosss hatchet (CH) and bundle arrangement. This is again statistically significant (P=0.031).While examining the orientation of collagen fibres in WDSCC 71.43% and in MDSCC, 83.33% had parallel orientation whereas in PDSCC 75% showed non parallel orientation. This orientation is statistically significant (p.008). On comparing the nature of birefringence maximum cases of WDSCC (85.71%) and MDSCC (83.33%) revealed strong birefringence whereas in PDSCC 75% exhibited weak. (statistically significant p.001). Conclusion: PSR stain under polarising microscope is an adjunct to the routine staining for studying stromal changes. The colour, arrangement, orientation & birefringence changes reflect its gradual shift from WDSCC to PDSCC and may help as a diagnostic and prognostic tool in OSCC.